Effect of Different Heat Treatments on the Degradation of Salmonella Nucleic Acid. Issue 4 (16th October 2013) - Li, Miaoyun; Zhao, Gaiming; Liu, Jie; Gao, Xiaoping; Zhang, Qiuhui
Abstract The effect of different heat treatments commonly used in the processing and consumption of food products on the detection and extinction of Salmonella nucleic acid were explored. Genomic DNA and RNA with different heat treatments were extracted at intervals and analyzed by agarose gel electrophoresis and real‐time polymerase chain reaction (PCR). The results showed that there was a large number of slowly degrading genomic DNA remained in the dead bacterial suspensions which had been treated with 65C/20 min and 85C/30 min, and DNA bands were still visible after 18 days; the DNA bands were very weak and disappeared after 4 days by boiling for 3 min. The 121C/15 min treated Salmonella had no visible DNA bands. The RNA bands of Salmonella were completely degradation initially in different heat treatments. The higher heating temperature and longer heat times Salmonella caused, the faster DNA degenerated. Therefore, DNA was not suitable for the quantitative detection and RNA was suitable for the qualitative detection during the detection of Salmonella by real‐time PCR/ reverse transcription PCR after heat treatments. The study may contribute to the successful application of Salmonella detection by nucleic acid in foods, since false positive of pathogens with PCR after heat treatments of food. Practical Applications This study demonstrated that PCR can result in the false positive of pathogens after heat treatments of food based on DNA. RNA was suitable for the qualitative detection during the detection of Salmonella by PCR with different heat treatments. It is of importance to detect Salmonella in food by nucleic acid after heat treatments.